Association of Postural Sway with Disability Status and Cerebellar Dysfunction in People with Multiple Sclerosis: A Preliminary Study - McLoughlin, James (Int J MS Care, 2015)
Background: The aims of this study were 1) to examine postural sway in the eyes open (EO) and eyes closed (EC) conditions in people with multiple sclerosis (MS) with moderate levels of disability compared with controls and 2) to examine relationships between postural sway and total Expanded Disability Status Scale (EDSS) scores, functional system subscores, and clinical measures of strength and spasticity in the MS group. Methods: Thirty-four people with moderate MS and ten matched controls completed measures of postural sway with EO and EC, knee extension and ankle dorsiflexion isometric strength, EDSS total score and subscores, and spasticity levels. Results: Participants with MS swayed significantly more with EO and EC and had reduced knee extension and ankle dorsiflexion strength compared with controls (P < .001). In the MS group, increased sway was associated with higher total EDSS scores and cerebellar function subscores, whereas increased sway ratio (EC/EO) was associated with reduced sensory function subscores. Postural sway was not significantly associated with strength or spasticity. Conclusions: Participants with MS swayed more and were significantly weaker than controls. Cerebellar dysfunction was identified as the EDSS domain most strongly associated with increased sway, and sensory loss was associated with a relatively greater dependence on vision for balance control. These findings suggest that exercise interventions targeting sensory integration and cerebellar ataxia may be beneficial for enhancing balance control in people with MS.